FAM13A affects body fat distribution and adipocyte function - Mohsen Fathzadeh (Nature Portfolio, 2020)
Genetic variants in the FAM13A locus have been associated with anthropometric and glycemic traits. Here, using fine-mapping, in vitro knockdown studies in pre-adipocytes and in vivo knockout in mice, the authors show that FAM13A is involved in regulating fat distribution and metabolic traits.